Formulas for the Euler-Mascheroni constant - Panzone, Pablo Andres (2009)
We give several integral representation for the Euler- Mascheroni constant using a combinatorial identity for sum_{n=1}^N 1/(n+x)(n+y). The derivation fo this combinatorial identity is done in an elementary way.